1999
DOI: 10.1046/j.1460-2695.1999.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and evolution of short fatigue cracks

Abstract: Distinguishing the different contributions to fatigue damage of short cracks having different sizes and locations on the specimen surface, three new concepts, referred to as effective short fatigue cracks (ESFCs), dominant effective short fatigue cracks (DESFC), and density of ESFCs, respectively, are introduced to facilitate an understanding of the mechanism of interaction and evolution of short cracks. These concepts are interrelated and in conjunction produce an ‘effective short fatigue crack criterion’. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Because the fatigue crack initiation took place in the weld metal for all the weld specimens in this study, no attention was paid to the heat‐affected zone. As indicated by Zhao et al 4,5 for welded joints of 1Cr–18Ni–9Ti stainless steel, the fatigue cracks always initiate at the boundaries of δ ferrite and matrix on the specimen surface of weld metal. Radaj et al 1 show that the endurance limit values of the heat‐affected zone are markedly higher than the base metal values for steel StE355 because of the hardening effect.…”
Section: Methodsmentioning
confidence: 86%
“…Because the fatigue crack initiation took place in the weld metal for all the weld specimens in this study, no attention was paid to the heat‐affected zone. As indicated by Zhao et al 4,5 for welded joints of 1Cr–18Ni–9Ti stainless steel, the fatigue cracks always initiate at the boundaries of δ ferrite and matrix on the specimen surface of weld metal. Radaj et al 1 show that the endurance limit values of the heat‐affected zone are markedly higher than the base metal values for steel StE355 because of the hardening effect.…”
Section: Methodsmentioning
confidence: 86%
“…In the description of the crack growth we have adopted the earlier concept 13 of an equivalent crack typical of an applied plastic strain amplitude. A similar concept was adopted later by Zhao et al 23 The length of an equivalent crack is equal to the instantaneous longest crack in the area of observation. The equivalent crack in our steel in the majority of cases was identical to the single real growing crack.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…It has been shown that the DESFC growth behaviour is a result of interactive short cracks, and this behaviour should be deemed suitable to describe the collective behaviour of short cracks 13 . Figure 10 shows variations of the DESFC growth rates in five specimens under different loading levels.…”
Section: Microstructural Effectsmentioning
confidence: 99%
“…The present work attempts to reveal the microstructural effects driving short‐crack growth in 1Cr18Ni9Ti stainless weld metal smooth specimens, which were machined from a welded pipe of mixed microstructure during low‐cycle fatigue, therefore it is difficult to distinguish the grains and measure the grain diameter. An experimental study of this material 12 , 13 has been recently undertaken into the mechanism of interaction and evolution of short fatigue cracks. In that study, three new concepts, referred to as effective short fatigue cracks (ESFCs), a dominant effective short fatigue crack (DESFC), and the density of ESFCs, respectively, were introduced to facilitate an understanding of the mechanism of interaction and evolution of short cracks.…”
Section: Introductionmentioning
confidence: 99%